Conductas adaptativas de un adolescente de 16 años en aislamiento a causa del covid19 - Chaso Caluña, Patricia Veronica (2020)
The objective of the present case study was to determine the adaptive behaviors of a 16-year-old adolescent in isolation due to covid.19 This problem is characterized by the presence of recurrent patterns of behavior due to the confinement that is past throughout the world, thus determining the diagnostic criteria and establishing the psychotherapist intervention through applications of techniques applied in patient sessions, such as the semi-structured clinical interview, clinical interview and psychometric tests, the analysis of this allows confirming a diagnosis of adjustment disorder. The affected areas are cognitive, affective, social-behavioral and somatic and in this way, we worked with the Cognitive-Behavioral model with the relaxation technique and schedule of activities with the family.